Construction of a Highly Sensitive Thiol‐Reactive AIEgen‐Peptide Conjugate for Monitoring Protein Unfolding and Aggregation in Cells. Issue 24 (24th October 2021) - Sabouri, Soheila; Liu, Mengjie; Zhang, Shouxiang; Yao, Bicheng; Soleimaninejad, Hamid; Baxter, Amy A.; Armendariz‐Vidales, Georgina; Subedi, Pramod; Duan, Chong; Lou, Xiaoding; Hogan, Conor F.; Heras, Begoña; et al.
Abstract: Impairment of the protein quality control network leads to the accumulation of unfolded and aggregated proteins. Direct detection of unfolded protein accumulation in the cells may provide the possibility for early diagnosis of neurodegenerative diseases. Here a new platform based on a peptide‐conjugated thiol‐reactive aggregation‐induced emission fluorogen (AIEgen), named MI‐BTD‐P (or D1), for labeling and tracking unfolded proteins in cells is reported. In vitro experiments with model proteins show that the non‐fluorescent D1 only becomes highly fluorescent when reacted with the thiol group of free cysteine (Cys) residues on unfolded proteins but not glutathione or folded proteins with buried or surface exposed Cys. When the labeled unfolded proteins form aggregates, D1 fluorescence intensity is further increased, and fluorescence lifetime is prolonged. D1 is then used to measure unfolded protein loads in cells by flow cytometry and track the aggregate formation of the D1 labeled unfolded proteins using confocal microscopy. In combination with fluorescence lifetime imaging technique, the proteome at different folding statuses can be better differentiated, demonstrating the versatility of this new platform. The rational design of D1 demonstrates the outlook of incorporation of diverse functional groups to achieve maximal sensitivity and selectivity in biological samples. Abstract : Proteostasis balance is central to maintenance of protein structures and functions and has been found to link to a variety of diseases, especially neurodegeneration. In this project, a new design strategy for synthesizing bio‐thiol fluorescent probes for quantitation and visualization of unfolded proteins and protein aggregations in cells is reported.